Gender-based differential item function for the positive and negative semantic dimensions of the relationship satisfaction scale with item response theory - Fung, Sai-Fu (2024)
Relationship satisfaction is at the core of a robust social life and is essential to mental health. The positive and negative semantic dimensions of the relationship satisfaction (PN-SMD) scale is considered in the field of relationship studies to be a reliable tool for assessing the quality of a person's interpersonal relationships. This study evaluated the psychometric properties of the PN-SMD scale by conducting multidimensional item response theory (MIRT) and differential item functioning (DIF) analyses, both of which are emerging assessment methods that focus on individual items. We recruited 511 Chinese undergraduate students for this study. Construct validity, internal consistency, and concurrent validity were assessed, and MIRT and DIF analyses were conducted. Five of the 14 items were found to have gender-based DIF traits, affecting the scale's construct validity. A revised nine-item scale (DIF items excluded) had a significantly better model fit and demonstrated comparable concurrent validity to the original scale. The implications of our results and future research directions are discussed.